Neurotransmitters involved in fast excitatory neurotransmission directly activate enteric glial cells. Issue 2 (2nd January 2013) - Boesmans, W.; Cirillo, C.; Van den Abbeel, V.; Van den Haute, C.; Depoortere, I.; Tack, J.; Vanden Berghe, P.
Abstract Background The intimate association between glial cells and neurons within the enteric nervous system has confounded careful examination of the direct responsiveness of enteric glia to different neuroligands. Therefore, we aimed to investigate whether neurotransmitters known to elicit fast excitatory potentials in enteric nerves also activate enteric glia directly. Methods We studied the effect of acetylcholine (ACh), serotonin (5‐HT), and adenosine triphosphate (ATP) on intracellular Ca2+ signaling using aequorin‐expressing and Fluo‐4 AM‐loaded CRL‐2690 rat and human enteric glial cell cultures devoid of neurons. The influence of these neurotransmitters on the proliferation of glia was measured and their effect on the expression of c‐Fos as well as glial fibrillary acidic protein (GFAP), Sox10, and S100 was examined by immunohistochemistry and quantitative RT‐PCR. Key Results Apart from ATP, also ACh and 5‐HT induced a dose‐dependent increase in intracellular Ca2+ concentration in CRL‐2690 cells. Similarly, these neurotransmitters also evoked Ca2+ transients in human primary enteric glial cells obtained from mucosal biopsies. In contrast with ATP, stimulation with ACh and 5‐HT induced early gene expression in CRL‐2690 cells. The proliferation of enteric glia and their expression of GFAP, Sox10, and S100 were not affected following stimulation with these neurotransmitters. Conclusions & Inferences We provide evidence that enteric glial cells respond to fast excitatory neurotransmitters by changes in intracellular Ca2+. On the basis of our experimental in vitro setting, we show that enteric glia are not only directly responsive to purinergic but also to serotonergic and cholinergic signaling mechanisms.